Drought legacy effects on fine-root-associated fungal communities are modulated by root interactions between tree species - Danzberger, Jasmin; Werner, Ramona; Mucha, Joanna; Pritsch, Karin; Weikl, Fabian (Frontiers in Forests and Global Change, 2023)
With climate change, the frequency of severe droughts is predicted to increase globally, resulting in increased forest dieback. Although fine-root systems and their associated fungi are considered crucial for tree nutrient exchange after a drought period and consequently for tree recovery, post-drought dynamics remain poorly understood. We rewatered mature European beech and Norway spruce after a 5-year experimental summer drought to shed light on belowground recovery processes. Therefore, we tracked the fine-root parameters growth, vitality, and mycorrhization in monospecific rooting zones with intraspecific root contact and mixed rooting zones with interspecific root contact of both tree species during the first 3 months of recovery, and we analyzed compositions of their root-associated fungal communities by DNA- and RNA-ITS2 sequencing. During recovery, the fine-root parameters differed between both tree species, with only minor effects of the tree rooting zone. Root-associated fungal communities showed no significant response to irrigation within 3 months after drought release. The rooting zone was the dominating factor affecting the root-associated fungal diversity, the abundance of trophic modes, and the response of individual saprotrophic and ectomycorrhizal (ECM) species. Furthermore, an analysis of the most abundant fungal species revealed that for ECM fungi, drought tolerance was common and for saprotrophs, a facultative, root-associated lifestyle. These results suggest that tree species-specific fungal communities are stable despite previous long-term drought and are closely associated with tree species-specific response patterns related to root survival and recovery. Moreover, an association between saprotrophic fungi and roots might be a strategy to support fungal drought survival.